A Sampling of Canadian Practice in Managing Nonvariceal Upper Gastrointestinal Bleeding before Recent Guideline Publication: Is there Room for Improvement? - Karen Bensoussan; Carlo A Fallone; Alan N Barkun; Myriam Martel (Canadian Journal of Gastroenterology)
BACKGROUND: There are few recent published consensus guidelines regarding nonvariceal upper gastrointestinal bleeding. In 2003, the Canadian Association of Gastroenterology sponsored a set of 20 recommendations. AIM: To compare current Canadian clinical practice patterns with these most recent guidelines.